2020
DOI: 10.1371/journal.pone.0228220
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon Merbok induced upwelling impact on material transport in the coastal northern South China Sea

Abstract: Typhoons frequently affect the South China Sea (SCS), playing an important role in changing the coastal marine system. To determine which process has the greatest impact on material transport in the coastal marine area during a typhoon, the sea temperature, salinity, concentration of nutrients, chlorophyll-a, total suspended matter, and δ 13 C of particulate organic carbon (δ 13 C-POC) in the water column of coastal Northern SCS (NSCS) were measured during two cruises in June 2017, in the pre-and post-typhoon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Jiang et al. (2020) suggested that enhanced vertical mixing after a typhoon was the dominant process changing the nutrient distribution in the coastal region of the northern SCS. However, the vertical distribution of phytoplankton in response to the combined influences of typhoons, upwelling, and river discharge still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al. (2020) suggested that enhanced vertical mixing after a typhoon was the dominant process changing the nutrient distribution in the coastal region of the northern SCS. However, the vertical distribution of phytoplankton in response to the combined influences of typhoons, upwelling, and river discharge still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, typhoon‐induced rain enhances runoff/river discharge, introducing a large amount of terrestrial organic matter and anthropogenic organic matter into coastal and estuarine systems (Chen & Li, 2002; Jiang et al., 2020; Xue et al., 2000). Enhanced discharge can also cause complete flushing, with considerable damage to mariculture activities in coastal and estuarine systems (Herbeck et al., 2011; Peng et al., 2016; Stevens et al., 2006; Yang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The dark blue dashed lines denote the paths of typhoon Merbok (sourced from the southeastern part of SCS on June 9 th , 2017, adapted from Jiang et al, 2020) and Mun (sourced from the eastern part of the SCS on July 1 st , 2019, adapted from Sun et al, 2021). At the mega stations, high vertical resolution water samples were taken at a depth interval of 10 m within the Ez.…”
Section: Sample Collectionmentioning
confidence: 99%